Evaluating the Lethal Toxicity of Eucalyptus and Yarrow Essential Oils against the House Fly (Musca domestica L.) under Laboratory Conditions - Majid Rashidi; Elham Jahanifard; Aboozar Soltani; Mona Sharififard (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: The house fly, Musca domestia L., is one of the most common health pests around the world, and its control is important due to the transmission of human pathogens, especially in unfavorable health conditions. Considering that plant essential oils are appropriate alternative to organic chemical insecticides, the present study aimed to investigate the effect of the essential oils of eucalyptus and yarrow in controlling the house flies. Methods: The essential oils of yarrow (Achillea millefolium) and eucalyptus (Eucapyptus glbulus) were extracted using a distillation apparatus. Concentrations of 5%, 10%, 15%, 20%, and 25% of the essential oils were prepared separately. Male and female house flies aged 2-3 days were exposed separately to the essential oils using spraying, treated surface, and bait methods. The collected data were analyzed using ANOVA and probit analysis in SPSS 24 software. Results: The obtained findings showed that spraying yarrow and eucalyptus essential oils had better efficacy against the house fly with LC50 values of 9.8% and 10.8% and LC90 values of 25.1% and 29.8%, respectively, compared to the treated surface and bait methods. Conclusion: The essential oils of eucalyptus and yarrow plants have potential to control the house flies in human dwellings due to their lethal properties and high safety. However, to use these essential oils as insecticidal compounds for house fly control, more research under field conditions is needed.